Targeting Natural Killer Cells for Tumor Immunotherapy - Zhang, Cai; Hu, Yuan; Shi, Chongdeng (Frontiers in Immunology, 2020)
Natural killer (NK) cells are important innate cytotoxic lymphocytes with rapid and efficient capacity to recognize and kill tumor cells. In recent years, adoptive transfer of autologous or allogeneic activated NK cells is becoming a promising cellular therapy for cancer. However, the therapeutic efficiency is encouraging only in hematopoietic malignancies but disappointing in solid tumors. There are some considerable challenges in the use of NK cell based therapies against solid tumors. It is difficult for NK cells to traffick and infiltrate into the tumor sites. The tumor microenvironment impairs the phenotype, activation, persistence and function of NK cells, even rendering NK cells dysfunction or exhaustion. Many strategies focus on attempts to improve the activation, durable persistence, and cytolytic activity of NK cells, including activation with cytokines or analogues. Modifying with chimeric antigen receptors (CAR) further increases the targeting specificity of NK cells. Checkpoint blockades can relieve the exhausted states of NK cells. In this review, we discuss the impact of the tumor microenvironment on effector and cytolytic function of NK cells, and summarize the various NK cell-based immunotherapeutic strategies, particularly, the recent advances in overcoming the suppression of tumor microenvironment to improve the clinical outcome of NK cell based immunotherapy against solid tumors.